Auditing Good Government in Africa : Public Sector Reform, Professional Norms and the Development Discourse - Gustavson, Maria; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
This book gives a comprehensive overview of the literature on development in Sub-Saharan Africa, and challenges the notions of African public officials presented there. It focuses on public audit institutions and offers rich empirical research results, which contradicts many assumptions made in the literature on development in Sub-Saharan Africa.
Keywords: Social sciences; Political theory; Public policy; Africa -- Politics and government; Political philosophy; Social policy; Economic policy; Development Policy; Political Philosophy; African Politics